The Role of Coordinate Systems, Coordinates and Heights in Horizontal Datum Transformations - Featherstone, Will; Vanicek, P. (The Institution of Surveyors, Australia Inc., 1999)
This paper reviews the fundamental definitions of geodetic and geocentric coordinate systems, whilst clarifying the distinction between coordinates and coordinate systems. It is then argued that the transformation of coordinates from a local geodetic datum to a geocentric datum should first employ a change of the coordinate system using a six- or four-parameter transformation, followed by further modelling of the distortion in the coordinates. It is also argued that the horizontal coordinate transformation should not include height information, since this forms an entirely different coordinate in another coordinate system.